Hubungan Postur Kerja dan Getaran Mekanis dengan Keluhan Musculoskeletal Disorder Pekerja PT. BMSTI - Yulia Sari; Perdani Ningrum; Isna Qadrijati (Disease Prevention and Public Health Journal, 2020)
Background: one of the problems related to the health of workers is musculoskeletal disorder. Risk factors for musculoskeletal disorders include occupational posture and mechanical vibration. This study investigates the relationship between musculoskeletal disorder complaints with work posture and mechanical vibration. Method: The study aims to determine the relationship between work posture and the incidence of musculoskeletal disorders. This research is an observational analysis with cross-section approaches, samples of this research using the total working population of 110 units of spinning workers in the PT Bintang Makmur Sentosa Textile Industry (BMSTI). Data collection techniques with observations and filling questionnaires. Worker posture and mechanical vibration were measured by the REBA assessment method, as well as the occurrence of musculoskeletal disorders (MSDs) complaints measured via the Nordic Body map (NBM) sheet filling. Â Data was analyzed using the Spearman correlation test. Results: Spearman test correlation suggests that there is a significant link between the musculoskeletal disorder complaints with the work posture p=0.000; r=0.819 and mechanical vibration p=0.000; r=0.951. The influence of work posture and mechanical vibration in the complaint of musculoskeletal disorders as much as 91.8%. Conclusion: there are a significant relationship and influence between work posture and mechanical vibration with the complaint of musculoskeletal disorders.